GROW Coaching as a Strategy to Enhance Personal Commitment in Professional Development a Literature Study - Tuti Herawati; Neila Aisha (LPPM Sekolah Tinggi Ilmu Ekonomi Ganesha, 2026)
Professional development requires not only technical competence and increased knowledge, but also a strong personal commitment to achieving long-term goals. In various professional contexts, individuals often experience difficulties in maintaining consistency, motivation, and responsibility for their self-development and career. Therefore, an effective coaching approach is needed to strengthen individual commitment on an ongoing basis. This study aims to analyze the role of the GROW coaching model as a strategy in increasing personal commitment to professional development through a literature study approach. The study used a qualitative descriptive method with a narrative literature review approach through a review of various scientific journals, books, and academic publications related to GROW coaching, personal commitment, self-awareness, and professional development. The results of the study indicate that the GROW model, consisting of Goal, Reality, Options, and Will, contributes significantly to the formation of self-awareness, intrinsic motivation, a sense of responsibility, and ownership of personal goals. The